Storycraft : the art of spiritual narrative - Wangerin, Walter (Fortress Press : 1517 Media, 2022)
In Storycraft: The Art of Spiritual Narrative, celebrated author Walter Wangerin Jr. illustrates the power of well-told stories and shows how important embracing story is as an essential tool for preaching and teaching the gospel. The book offers a theology of story that is profoundly incarnational as the Word takes on flesh in practiced speech. In Storycraft, renowned author Walter Wangerin Jr. explores the power of narrative and storytelling to impact message, messenger, and hearer. Through preaching and teaching, the gospel comes alive--is incarnated--in the words, actions, and stories we tell. Well-crafted stories shape the relationship between tellers and listeners, between preachers and people. And in the telling, trust is established, faith is formed, and lives change.